Enjoy Your Enemy or how the Kosovo (Media) War Broke Out - B. Hrvatin, Sandra; Trampuž, Martina (Javnost-The Public, 2000)
The present article analyses modes and reasons lying behind media construction and production of war in Serbia and Kosovo. By using the film Wag the Dog, the authors reveal the role of media including not only reporting about but the construction of wars as well. Media have power to create events that state authority needs for operation. Serbian media have nationalised, mobilised and emotionalised the public sphere by the use of techniques of so called "patriotic journalism" and by making historical myths a topical subject. The prevailing belief of media being the real trigger for war in Kosovo does not hold true. Its roots should be traced back to the eighties when Serbian authority deliberately started to spread Serbian nationalism and to the nineties, when implementation of the new media legislation took place and when the abuse of media started.